Analysis of The Parenting Method used by Working Parents in Shaping Children's Personality - Mei Nita Hutauruk; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2023)
The objective of this study is to determine the type of career parenting and its impact on the development of children's personalities. The descriptive phenomology method is used in this study. The study was conducted out in Sibolga City, Hutabarangan Village, and Sibolga Julu. Three youngsters aged 12 to 14 years old, as well as their parents, participated in the study. Unstructured interviews and observations are used to acquire data. The data analysis method employed is qualitative descriptive data analysis. According to the findings of this study, the parenting style of career parents has a substantial impact on the personalities of their children. A qualitative investigation of three parents who worked as small merchants, restaurant employees, and factory workers revealed disparities in parenting approaches, namely democratic and permissive. In this instance, it is critical for working parents with limited time to find methods to be actively involved in their children's life. For example, regular communication, listening to children's feelings, and spending quality time together can all help.